Rotor Position Sensorless Control of BLDC Motor based on Back Emf Detection Method - M. Murugan; R. Jayabharath; C. Gurunathan (Institute of Advanced Engineering and Science, 2015)
In this paper an improved back emf detection method is proposed. The motor neutral voltage is elemenated and the phase back emf zero crossing point can be directly extracted by detecting voltage difference between the phase terminal and the midpoint of the dc link. Here filtering circuit is not needed and the BLDC motor is provided with PWM control of 100% duty ratio which is presented in this paper. To perform the inverter commutation, there is a need of six commutation signals which is obtained by sensing only one of the three phase terminals that reduces the cost of the sensing circuit. The reduction of the imbalance in the six commutation signals which are caused by the asymmetrical behavior of the three phase windings in BLDC motor had been reduced in a varied speed range. It simplifies the starting procedure and achieve the motor performance over a wide speed range. This proposed method is analyzed through the simulation results using MATLAB Simulink. DOI: http://dx.doi.org/10.11591/telkomnika.v14i2.7423